Circuits of Sexist and Sexual Male Violence. Notes to Think about its Productive Circulation at the University (UNAM) - Mauricio Zabalgoitia Herrera (Feminismo/s, 2025)
This article problematizes three sexist expressions that stand out for their recurrence as everyday resources used by men. They were obtained from field work carried out with female students in a workshop at the FFyL of the UNAM (Mexico). As a starting point, studies on sexism in public life as well as in the university are recovered. The initial objective is to show that sexist expressions are inserted in chains that link resources and at the same time configure scales of gravity. In addition, it seeks to show how their use sustains and promotes normative masculinity. The methodology includes a four-phase analysis: in the first, the chains connect sexism as ritual energy with the symbolic and mythical assumptions of machismo and misogyny. In the second, sexist forms are presented as acts that produce effects on women and maintain, among other issues, ideals about male sexuality. In this way, from the everyday resource, the circuits are constantly reinitiated. It is proposed that this circularity is productive because it supports practices whose purpose is the maintenance of a domination order based on the power of sexist and sexual male violence, in addition to containing, sanctioning, and controlling women in all spheres. With this, the third phase addresses some of the gains, losses and privileges that occur in the web of chains and circuits. Finally, it is proposed that the circuits of sexist and sexual male violence are reactivated under an action involving the associative hierarchy of masculinity. It is a reset button that is pressed at each sexist act so that the circularity continues to function and so that young men are enrolled in an encyclopedia of normative masculinity.